Macroporous pseudo-boehmite and a method for its preparation

CN122877784APending Publication Date: 2026-10-09YUEYANG HUIJING NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611100306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这种狭小的孔道结构在处理重油、渣油等大分子化合物时,极易产生严重的传质扩散阻力,导致大分子难以进入孔道内部进行有效反应,限制了催化剂在重油加氢、大分子裂化等领域的应用效能

Benefits of technology

本发明通过复合模板剂与老化发泡的协同作用,成功构建了以大孔为主导的多级孔道结构,显著提升了材料对大分子物质的传质扩散能力。采用拟薄水铝石滤饼与可溶性铝盐复配的铝源体系,并引入柠檬酸铵等稳定剂,抑制了铝盐水解过程中的晶粒团聚,保障了组分的分散均匀性。软模板剂(聚醚类非离子表面活性剂与木质素磺酸盐)与硬模板剂(纳米级无机刚性粒子与高分子分散剂)的组合使用,在沉淀过程中为大孔结构的形成提供了稳定的模板导向;而复合沉淀剂中快速与缓慢水解组分的配比调控,则实现了沉淀物的均匀成核与可控生长。老化阶段加入的发泡助剂(如过氧化氢、碳酸氢铵)在密闭高温条件下分解释放气体,配合二次扩孔介质的渗透溶胀作用,进一步拓展了孔道尺寸并优化了孔道连通性。喷雾干燥工艺结合干燥助剂的添加,确保了球形微粉的良好形貌与结构稳定性,后续阶梯式煅烧则在去除模板剂的同时,避免了孔结构的坍塌,最终获得的大孔拟薄水铝石兼具高比表面积、适宜的孔容及优异的热稳定性,为其在重油催化、大分子吸附等领域的应用奠定了关键材料基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a macroporous pseudo-boehmite and a preparation method thereof, and belongs to the technical field of inorganic materials. The preparation method comprises the following steps: S1: mixing an aluminum source with a solvent, adding a stabilizer, and stirring to form an aluminum source dispersion liquid; S2: adding a composite template agent to the aluminum source dispersion liquid to obtain a composite emulsion; S3: carrying out a parallel flow neutralization precipitation reaction on the composite emulsion and a composite precipitator to obtain a slurry containing a precipitate; S4: adding a foaming aid to the slurry, and carrying out aging under a closed condition to obtain an aged slurry; S5: after washing the aged slurry, carrying out spray drying to obtain spherical micro powder; and calcining the spherical micro powder to obtain the macroporous pseudo-boehmite. Through the process of combining the composite template agent, the composite precipitator, the foaming aid and the aging, the pore structure of the pseudo-boehmite can be effectively controlled, the proportion of macropores can be significantly increased, and thus the macroporous pseudo-boehmite product with excellent performance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of inorganic materials technology, and in particular to a macroporous pseudoboehmite and its preparation method. Background Technology

[0002] Boehmite, as an important transition-state alumina precursor, is widely used in petrochemical catalyst supports, adsorbents, and ceramic materials due to its high specific surface area, good tunability of pore structure, and excellent colloidal properties. In catalytic applications, the pore structure of the support (including pore size, pore volume, and pore distribution) directly determines the dispersion of the active component, the mass transfer and diffusion efficiency of reactants and products, and thus affects the activity, selectivity, and lifespan of the catalyst.

[0003] Currently, the main industrial methods for preparing boehmite include neutralization (such as acid and alkali methods), aluminum alkoxide hydrolysis, and carbonization. Boehmite prepared by conventional neutralization or carbonization methods has a pore structure primarily formed by the accumulation of nanoscale grains, with pore sizes mostly concentrated in the micropore or mesopore range of 3-8 nm. Although some aluminum alkoxide hydrolysis methods can achieve larger pore sizes, they are costly and difficult to scale up industrially. In products prepared by existing technologies, macropores (>50 nm) account for a very low percentage, or even almost none. This narrow pore structure easily generates severe mass transfer and diffusion resistance when processing large molecular compounds such as heavy oil and residual oil, making it difficult for large molecules to enter the pores for effective reactions, thus limiting the catalyst's application efficiency in heavy oil hydrogenation, macromolecular cracking, and other fields. Traditional processes typically rely on only a single soft or hard template agent for pore structure control, making it difficult to construct multi-level pore structures. A single pore type not only reduces the effective utilization rate of specific surface area, but also, during subsequent drying and calcination, due to the capillary force, the pores between nanocrystals are prone to collapse or shrinkage, resulting in a significant decrease in specific surface area and pore volume, and poor product thermal stability. Summary of the Invention

[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a macroporous pseudoboehmite and a method for preparing the same.

[0005] Specifically, the first aspect of this application provides a method for preparing macroporous pseudoboehmite, comprising the following steps: S1: Mix the aluminum source with the solvent, add the stabilizer, and stir to form an aluminum source dispersion; S2: Add a composite template agent to the aluminum source dispersion and disperse it evenly to obtain a composite emulsion; the composite template agent includes a soft template agent and a hard template agent; the soft template agent includes a combination of polyether nonionic surfactant and lignin sulfonate; the hard template agent includes a combination of nano-sized inorganic rigid particles and polymeric dispersant; S3: The composite emulsion and the composite precipitant are subjected to a co-current neutralization and precipitation reaction, with the reaction pH controlled at 6.8-7.2 and the reaction temperature at 60-70℃, to obtain a slurry containing precipitate; S4: Add a foaming agent to the slurry and age it under closed conditions. The aging temperature is 130-150℃ and the aging time is 2-5h to obtain an aged slurry. S5: After washing the aged slurry, spray dry it to obtain spherical micro powder; calcine the spherical micro powder to obtain macroporous pseudoboehmite.

[0006] Further, the aluminum source in step S1 comprises a mixture of boehmite filter cake and soluble aluminum salt, wherein the mass ratio of the boehmite filter cake to the soluble aluminum salt is 1.8-2.2. The stabilizer is at least one of ammonium citrate, citric acid, or ethylenediaminetetraacetic acid.

[0007] Furthermore, the polyether nonionic surfactant is polyethylene glycol or a polyoxyethylene-polyoxypropylene block copolymer; the lignin sulfonate is at least one of sodium lignin sulfonate, calcium lignin sulfonate, or ammonium lignin sulfonate. The nanoscale inorganic rigid particles are at least one of nano-silica, nano-alumina, or nano-titanium oxide, with a D50 of 10-50 nm; the polymeric dispersant is at least one of polyvinylpyrrolidone, polyethylene glycol, or polyacrylamide.

[0008] Further, the composite precipitant in step S3 comprises a combination of a fast hydrolysis precipitant and a slow hydrolysis precipitant; the fast hydrolysis precipitant is at least one of ammonium carbonate, ammonium bicarbonate or sodium carbonate; the slow hydrolysis precipitant is at least one of urea or hexamethylenetetramine; the mass ratio of the fast hydrolysis precipitant to the slow hydrolysis precipitant is 0.5-1.5:1.

[0009] Further, the foaming agent mentioned in step S4 is at least one of hydrogen peroxide, ammonium bicarbonate, or azodicarbonamide, and the amount added is 0.05%-0.5% of the total mass of the slurry; During the aging process, a secondary pore-expanding medium is added. The secondary pore-expanding medium is at least one of polyethylene glycol, polypropylene glycol, or glycerin, and the amount added is 0.1%-0.5% of the total mass of the slurry.

[0010] Furthermore, in step S5, the inlet air temperature of the spray drying is 200-210℃, the outlet air temperature is 90-100℃, and the atomizing disc rotation speed is 12000-18000rpm. Furthermore, a drying aid is added to the washed slurry before spray drying. The drying aid is at least one of polyvinyl alcohol, polyvinylpyrrolidone, or polyethylene glycol, and the amount added is 0.5%-1.5% of the dry basis mass.

[0011] Further, the calcination in step S5 involves heating to 250-300℃ at a rate of 1-5℃ / min and holding for 0.5-1.5h, then heating to 350-450℃ and holding for 1.5-3h.

[0012] The second aspect of this application provides a macroporous pseudoboehmite, prepared by the aforementioned preparation method.

[0013] The present invention has the following beneficial effects: This invention successfully constructs a multi-level pore structure dominated by macropores through the synergistic effect of composite template agents and aging foaming, significantly improving the material's mass transfer and diffusion capabilities for macromolecules. An aluminum source system combining pseudoboehmite filter cake and soluble aluminum salts, along with stabilizers such as ammonium citrate, inhibits crystal agglomeration during aluminum salt hydrolysis, ensuring uniform component dispersion. The combined use of soft template agents (polyether nonionic surfactants and lignin sulfonates) and hard template agents (nanoscale inorganic rigid particles and polymeric dispersants) provides a stable template for macroporous structure formation during precipitation; while the controlled ratio of fast and slow hydrolyzing components in the composite precipitant achieves uniform nucleation and controllable growth of the precipitate. Foaming aids added during the aging stage (such as hydrogen peroxide and ammonium bicarbonate) decompose and release gases under sealed high-temperature conditions, further expanding pore size and optimizing pore connectivity in conjunction with the permeation and swelling effect of the secondary pore-expanding medium. The spray drying process, combined with the addition of drying aids, ensures the good morphology and structural stability of the spherical micro powder. The subsequent step-calcination removes the template agent while avoiding the collapse of the pore structure. The resulting macroporous pseudoboehmite has a high specific surface area, suitable pore volume and excellent thermal stability, laying a key material foundation for its application in heavy oil catalysis, macromolecular adsorption and other fields. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0015] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0016] An embodiment of the first aspect of this application provides a method for preparing macroporous pseudoboehmite, comprising the following steps: S1: Mix the aluminum source with the solvent, add the stabilizer, and stir to form an aluminum source dispersion; S2: Add a composite template agent to the aluminum source dispersion and disperse it evenly to obtain a composite emulsion; the composite template agent includes a soft template agent and a hard template agent; the soft template agent includes a combination of polyether nonionic surfactant and lignin sulfonate; the hard template agent includes a combination of nano-sized inorganic rigid particles and polymeric dispersant; S3: The composite emulsion and the composite precipitant are subjected to a co-current neutralization and precipitation reaction, with the reaction pH controlled at 6.8-7.2 and the reaction temperature at 60-70℃, to obtain a slurry containing precipitate; S4: Add a foaming agent to the slurry and age it under closed conditions. The aging temperature is 130-150℃ and the aging time is 2-5h to obtain an aged slurry. S5: Centrifuge the aged slurry to dehydrate (4000 rpm, 10 min), redisperse the filter cake in deionized water, wash three times, and after the last wash, disperse the filter cake in an appropriate amount of deionized water, add polyvinyl alcohol (prepared as a 10 wt% solution), stir for 30 min, adjust the solid content to 25 ± 2%, and then spray dry to obtain spherical micro powder; calcine the spherical micro powder to obtain macroporous pseudoboehmite.

[0017] In this embodiment, the aluminum source in step S1 comprises a mixture of boehmite filter cake and soluble aluminum salt, wherein the mass ratio of the boehmite filter cake (on a dry basis) to the soluble aluminum salt is 1.8-2.2; the stabilizer is at least one of ammonium citrate, citric acid, or ethylenediaminetetraacetic acid. The boehmite filter cake is an industrial by-product with a solid content of 30% (source: a batch of macroporous boehmite products from our company whose pore size distribution and specific surface area deviated from internal control indicators). The soluble aluminum salt is aluminum nitrate or sodium aluminate.

[0018] Specifically, in step S1, the pseudoboehmite filter cake and sodium aluminate are added to water and stirred in a water bath at 40-50°C for 30 minutes at 300 rpm to form a uniform suspension; ammonium citrate is added to the above suspension, and stirring is continued for 20 minutes to allow Al to form a uniform suspension. 3+ Formation of citric acid complex, reducing free Al 3+ Concentration lays the foundation for subsequent precipitation rate control.

[0019] The soft template agent in step S2 comprises a combination of a polyether nonionic surfactant and a lignin sulfonate; the hard template agent comprises a combination of nanoscale inorganic rigid particles and a polymeric dispersant. Further, the polyether nonionic surfactant is polyethylene glycol or a polyoxyethylene-polyoxypropylene block copolymer; the lignin sulfonate is at least one of sodium lignin sulfonate, calcium lignin sulfonate, or ammonium lignin sulfonate; the nanoscale inorganic rigid particles are at least one of nano-silica, nano-alumina, or nano-titanium oxide, with a D50 of 10-50 nm; and the polymeric dispersant is at least one of polyvinylpyrrolidone, polyethylene glycol, or polyacrylamide.

[0020] Specifically, in step S2, polyethylene glycol PEG-4000 and sodium lignosulfonate are added to the aluminum source dispersion, and ultrasonic dispersion is carried out for 10 minutes at an ultrasonic frequency of 40 kHz and a power of 300 W, so that the soft template agent is uniformly adsorbed on the surface of the aluminum source particles; then nano-SiO2 and polyvinylpyrrolidone PVP-K30 are added, and high-speed shear emulsification is carried out at a speed of 8000 rpm for 5 minutes to form a composite emulsion.

[0021] The composite precipitant in step S3 comprises a combination of a fast hydrolysis precipitant and a slow hydrolysis precipitant; the fast hydrolysis precipitant is at least one of ammonium carbonate, ammonium bicarbonate or sodium carbonate; the slow hydrolysis precipitant is at least one of urea or hexamethylenetetramine; the mass ratio of the fast hydrolysis precipitant to the slow hydrolysis precipitant is 0.5-1.5:1.

[0022] Precipitant preparation: Dissolve urea and ammonium carbonate in water and stir until completely dissolved to obtain a composite precipitant solution.

[0023] The composite emulsion and composite precipitant solution obtained in step S2 were added to the reactor in parallel flow. The reaction temperature was controlled at 65℃, the feeding time was 90 min, and the stirring speed was 400 rpm. The amount of precipitant was controlled by adjusting the flow rate of the precipitant to maintain the pH of the reaction system between 6.8 and 7.2. The feed pumps for both were turned on simultaneously, with a feed rate ratio (emulsion:precipitant) of 1:0.8 (volume ratio). After the addition was completed, stirring was continued at 65℃ for 30 min to ensure complete precipitation.

[0024] The foaming agent mentioned in step S4 is at least one of hydrogen peroxide, ammonium bicarbonate or azodicarbonamide, and the amount added is 0.05%-0.5% of the total mass of the slurry; a secondary pore-expanding medium is also added during the aging process, and the secondary pore-expanding medium is at least one of polyethylene glycol, polypropylene glycol or glycerin, and the amount added is 0.1%-0.5% of the total mass of the slurry.

[0025] The slurry obtained in step S3 was transferred to a high-pressure reactor, and 30% H2O2 solution and polyethylene glycol PEG-200 were added and stirred until homogeneous. The aging temperature was 130-150℃, the aging time was 2-5 hours, and the stirring speed was 150 rpm. After aging, the mixture was allowed to cool naturally to below 60℃ before being discharged. In this step, H2O2 decomposes in a high-temperature, sealed environment to generate oxygen bubbles. These bubbles form bubble templates in the slurry, promoting the growth of precipitates around the bubbles and initially constructing a macroporous framework. Simultaneously, polyethylene glycol PEG-200 acts as a secondary pore-expanding medium, its molecular chains penetrating into the pore structure of the precipitate, further expanding the pore walls through swelling, reducing the risk of pore collapse, and significantly improving the proportion and connectivity of macropores.

[0026] In this embodiment, the inlet air temperature of the spray drying in step S5 is 200-210℃, the outlet air temperature is 90-100℃, and the atomizing disc rotation speed is 12000-18000rpm; before spray drying, a drying aid is added to the washed slurry, wherein the drying aid is at least one of polyvinyl alcohol, polyvinylpyrrolidone, or polyethylene glycol, and the amount added is 0.5%-1.5% of the dry basis mass.

[0027] The calcination process involves heating at a rate of 1-5℃ / min to 250-300℃ and holding at that temperature for 0.5-1.5 hours, followed by heating to 350-450℃ and holding at that temperature for 1.5-3 hours. This stepped heating calcination effectively avoids thermal shock collapse of the pore structure caused by rapid heating, allowing the template agent (soft template agent, hard template agent) to fully decompose and volatilize, ultimately yielding the target product with a high specific surface area and a well-developed macroporous structure.

[0028] The second aspect of this application provides a macroporous pseudoboehmite, prepared by the aforementioned preparation method.

[0029] Example The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight. Unless otherwise stated, all reagents used in the examples are available commercially or synthesized using conventional methods and are ready for use without further processing. Unless otherwise stated, all instruments used in the examples are available commercially.

[0030] Example 1 A method for preparing macroporous pseudoboehmite includes the following steps: S1: Add 200 parts of the aluminum source (200 parts of boehmite filter cake (on a dry basis) and 100 parts of sodium aluminate) to 400 parts of water, and stir in a 45°C water bath for 30 minutes at 300 rpm to form a uniform suspension; add 1 part of stabilizer (ammonium citrate) to the above suspension, and continue stirring for 20 minutes to form an aluminum source dispersion; S2: Add a soft template agent (4 parts polyethylene glycol PEG-4000 and 2 parts sodium lignosulfonate) to the aluminum source dispersion, and ultrasonically disperse for 10 min at a frequency of 40 kHz and a power of 300 W to ensure that the soft template agent is uniformly adsorbed on the surface of the aluminum source particles; then add a hard template agent (5 parts nano SiO2 and 1 part polyvinylpyrrolidone PVP-K30), and emulsify by high-speed shearing at a speed of 8000 rpm for 5 min to form a composite emulsion. S3: Preparation of precipitant: Dissolve the slow hydrolysis precipitant (10 parts urea) and the fast hydrolysis precipitant (10 parts ammonium carbonate) in 100 parts water and stir until completely dissolved to obtain a composite precipitant solution; The composite emulsion obtained in step S2 and the composite precipitant solution obtained in step S3 are added to the reactor in parallel flow and mixed. The temperature is raised to 65°C, the feeding time is 90 min, and the stirring speed is 400 rpm. The amount of precipitant is controlled by adjusting the flow rate of the precipitant. The pH of the reaction system is controlled between 6.8 and 7.2. The feed pumps of both are turned on at the same time, and the feed rate ratio (emulsion: precipitant) = 1:0.8 (volume ratio). After the feeding is completed, the mixture is stirred at 65°C for 30 min to ensure complete precipitation and obtain a slurry containing precipitate. S4: Transfer the slurry obtained in step S3 to a high-pressure reactor, add foaming agent (0.4 parts of 30% H2O2 solution by mass) and secondary pore-expanding medium (0.3 parts of polyethylene glycol PEG-200), and stir evenly; heat to 140℃ at 2℃ / min, stir at 150 rpm, and age for 3 hours. After aging, allow to cool naturally to below 60℃ and discharge to obtain aged slurry. Then wash with 10% NaOH solution at 60℃. S5: Centrifuge the alkaline-washed slurry to dehydrate (4000 rpm, 10 min). Redisperse the filter cake in deionized water and repeat the washing process three times. After the final wash, disperse the filter cake in an appropriate amount of water and add a drying aid (1.0 part polyvinyl alcohol (manufacturer: Shenzhen Beihua Fine Chemicals Co., Ltd.) (prepared as a 10 wt% solution)). Stir for 30 min to adjust the solid content to 25%. Then, perform spray drying. The inlet air temperature for spray drying is 200℃, the outlet air temperature is 100℃, and the atomizing disc speed is 15000 rpm to obtain spherical micro powder. Calcinate the spherical micro powder by heating from 25℃ to 280℃ at 3℃ / min and holding for 1 h, then heating to 400℃ at 4℃ / min and holding for 2.5 h to obtain macroporous pseudoboehmite.

[0031] Example 2 This embodiment is basically the same as Embodiment 1, except that 8 parts of nano-SiO2 and 1.5 parts of polyvinylpyrrolidone PVP-K30 are added in step S2.

[0032] Example 3 This embodiment is basically the same as Embodiment 1, except that 0.2 parts of 30% H2O2 solution are added in step S4.

[0033] Example 4 This embodiment is basically the same as Embodiment 1, except that 0.6 parts of 30% H2O2 solution are added in step S4.

[0034] Comparative Example 1 This comparative example is basically the same as Example 1, except that H2O2 solution is not added in step S4.

[0035] Comparative Example 2 This comparative example is basically the same as Example 1, except that sodium lignosulfonate and nano SiO2 are not added in step S2, but only 6 parts of polyethylene glycol PEG-4000 are added.

[0036] Comparative Example 3 This comparative example is basically the same as Example 1, except that in step S3, the pH of the reaction system is controlled between 6.0 and 6.5.

[0037] Comparative Example 4 This comparative example is basically the same as Example 1, except that only 200 parts of sodium aluminate are used in step S1, and boehmite filter cake is not used.

[0038] Experimental Case The following tests were conducted on the samples from Examples 1-4 and Comparative Examples 1-4: The specific surface area and pore volume of the sample material were calculated using a nitrogen physical adsorption instrument combined with the BET and BJH methods; the macropore (>50nm) distribution was measured using a mercury porosimeter, and the test results are shown in Table 1.

[0039] Table 1. Test results of samples from Examples 1-4 and Comparative Examples 1-4

[0040] As shown in Table 1, the macroporous pseudoboehmite prepared in Examples 1-4 all have high specific surface areas (278-301 m²). 2 / g), larger pore volume (1.12-1.52 cm³) 3 The proportion of macropores (>50nm) reached over 40%, fully demonstrating the significant advantages of the preparation method in constructing macroporous structures.

[0041] In contrast, Comparative Example 1, which did not include the foaming agent H2O2, had a macropore ratio of only 12%, which was much lower than that of the Example. The reason may be that the lack of oxygen bubbles generated by the decomposition of H2O2 during the aging process as bubble templates makes it impossible to effectively construct a macropore framework, resulting in a pore structure dominated by small and medium-sized pores.

[0042] Comparative Example 2 did not include sodium lignosulfonate or nano-SiO2, and only used polyethylene glycol PEG-4000 as a soft template agent. The macropore ratio was less than 5%, indicating that a single soft template agent is difficult to form a stable and well-developed macroporous structure. The addition of the hard template agent nano-SiO2 is crucial for the construction of rigid channels. Sodium lignosulfonate, as a synergistic soft template agent, may optimize the adsorption and dispersion of the template agent on the surface of aluminum source particles through synergistic effects with polyethylene glycol, thereby affecting subsequent precipitation and pore structure formation.

[0043] In Comparative Example 3, due to the lower pH, the supersaturation of aluminum precipitation increased, the nucleation rate accelerated significantly, the primary particles became finer, and the interparticle packing became more compact, thus increasing the specific surface area, but decreasing the proportion of macropores. Furthermore, because the primary particles were small and the packing structure was more dense, the pores were mainly micropores and mesopores, and the proportion of macropores (>50nm) decreased significantly, resulting in a marked decrease in pore volume. Template agents such as PEG / sodium lignosulfonate exhibited poorer adsorption conformation and site occupancy under lower pH conditions, making it difficult to form macroporous structures, further weakening the contribution of macropores.

[0044] Comparative Example 4 used only soluble aluminum salts as the aluminum source and did not add boehmite filter cake. Its macropore ratio was 33%, which was higher than some comparative examples, but still lower than Examples 1-4. This may be because the boehmite filter cake, as a seed crystal, provides growth sites for the precipitation reaction and helps to form a more regular and interconnected pore structure. At the same time, the use of industrial by-product filter cake also reduces production costs.

[0045] These results strongly demonstrate that the process of combining composite template agent, composite precipitant, foaming agent and aging can effectively control the pore structure of pseudoboehmite, significantly increase the proportion of macropores, and thus obtain high-performance macroporous pseudoboehmite products.

[0046] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing macroporous pseudoboehmite, characterized in that, Includes the following steps: S1: Mix the aluminum source with the solvent, add the stabilizer, and stir to form an aluminum source dispersion; S2: Add a composite template agent to the aluminum source dispersion and disperse it evenly to obtain a composite emulsion; the composite template agent includes a soft template agent and a hard template agent; the soft template agent includes a combination of polyether nonionic surfactant and lignin sulfonate; the hard template agent includes a combination of nano-sized inorganic rigid particles and polymeric dispersant; S3: The composite emulsion and the composite precipitant are subjected to a co-current neutralization and precipitation reaction, with the reaction pH controlled at 6.8-7.2 and the reaction temperature at 60-70℃, to obtain a slurry containing precipitate; S4: Add a foaming agent to the slurry and age it under closed conditions. The aging temperature is 130-150℃ and the aging time is 2-5h to obtain an aged slurry. S5: After washing the aged slurry, spray dry it to obtain spherical micro powder; calcine the spherical micro powder to obtain macroporous pseudoboehmite.

2. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, The aluminum source in step S1 comprises a mixture of boehmite filter cake and soluble aluminum salt, wherein the mass ratio of boehmite filter cake to soluble aluminum salt is 1.8-2.2:1; The stabilizer is at least one of ammonium citrate, citric acid, or ethylenediaminetetraacetic acid.

3. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, The polyether nonionic surfactant is polyethylene glycol or polyoxyethylene-polyoxypropylene block copolymer; the lignin sulfonate is at least one of sodium lignin sulfonate, calcium lignin sulfonate or ammonium lignin sulfonate. The nanoscale inorganic rigid particles are at least one of nano-silica, nano-alumina, or nano-titanium oxide, with a D50 of 10-50 nm; the polymeric dispersant is at least one of polyvinylpyrrolidone, polyethylene glycol, or polyacrylamide.

4. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, The composite precipitant in step S3 comprises a combination of a fast hydrolysis precipitant and a slow hydrolysis precipitant; the fast hydrolysis precipitant is at least one of ammonium carbonate, ammonium bicarbonate or sodium carbonate; the slow hydrolysis precipitant is at least one of urea or hexamethylenetetramine; the mass ratio of the fast hydrolysis precipitant to the slow hydrolysis precipitant is 0.5-1.5:

1.

5. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, The foaming agent mentioned in step S4 is at least one of hydrogen peroxide, ammonium bicarbonate, or azodicarbonamide, and the amount added is 0.05%-0.5% of the total mass of the slurry; During the aging process, a secondary pore-expanding medium is added. The secondary pore-expanding medium is at least one of polyethylene glycol, polypropylene glycol, or glycerin, and the amount added is 0.1%-0.5% of the total mass of the slurry.

6. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, In step S5, the inlet air temperature of the spray dryer is 200-210℃, the outlet air temperature is 90-100℃, and the atomizing disc rotation speed is 12000-18000rpm.

7. The method for preparing macroporous pseudoboehmite according to claim 6, characterized in that, A drying aid is added to the washed slurry before spray drying. The drying aid is at least one of polyvinyl alcohol, polyvinylpyrrolidone, or polyethylene glycol, and the amount added is 0.5%-1.5% of the dry basis mass.

8. The method for preparing macroporous pseudoboehmite according to claim 1, characterized in that, The calcination in step S5 involves heating at 1-5℃ / min to 250-300℃ and holding for 0.5-1.5h, then heating to 350-500℃ and holding for 1.5-3h.

9. A macroporous pseudoboehmite, characterized in that, Prepared by the preparation method according to any one of claims 1-8.